THE INFLUENCE OF WORK PRESSURE ON EMPLOYEE PERFORMANCE WITH WORKLOAD AS A MODERATING VARIABLE - Suryatman Desri; Widyastuti; Delyana Rahmawany Pulungan; Krisna Meidiyantoro Baharuddin; Aleksander Sakalessy (INJOSEDU: International Journal of Social and Education, 2025)
This study is a quantitative study with an explanatory approach. The data used in this article are primary data that researchers obtained from Ibox employees spread throughout Indonesia. The data obtained by researchers came from questionnaire items that were distributed containing 5 statement items, namely statements strongly agree, agree, normal, disagree, and strongly disagree which were analyzed using the smart PLS 4.0 analysis tool. The result in this article show that each variable used in this article is acceptable and ducbitika because the P-Value is positive and below the significance level of 0.05, which is 0.004. This is because the higher the internal work pressure owned by an employee can make employees more motivated so that they are more enthusiastic in working and ultimately can improve the Employee's Performance itself. In line with the first hypothesis, the second hypothesis also shows similar results if the Workload variable can strengthen the influence of Internal Work Pressure on Employee Performance, this is caused by the same thing, namely the P-Values which are positive and below the significance level of 0.05, namely 0.000, which is more significant than direct testing of 0.04. Thus it can be concluded that the first and second hypotheses in this article can be accepted and proven.